Towards the Development of a Multilingual Environment: A Case of a South African University - Vimbai Mbirimi-Hungwe (Journal of Languages and Language Teaching, 2023)
This paper presents an observational study conducted at one of the South African Universities, which is undergoing a transformation aimed at acknowledging and incorporating indigenous languages. While the positive response to the Language Policy of Higher Education (LPHE) is laudable, certain aspects of this transformation still fail to recognize the importance of indigenous languages as sources of knowledge. The primary objective of this paper is to shed light on scenarios where multilingualism, specifically through translanguaging, is acknowledged and utilized to enhance students' comprehension of academic materials, particularly for non-speakers of Setswana who are learning the language for communicative purposes. The findings of a focus group discussion revealed that multilingual students possess valuable funds of knowledge that deserve recognition in teaching and learning contexts. Consequently, this paper emphasizes the necessity of recognizing and utilizing multilingualism not only for communicative purposes but also for academic purposes. It advocates for the adoption of a translanguaging approach in teaching and acknowledges students' language practices as a means to provide access to social justice for multilingual students. In conclusion, this study underscores the importance of recognizing the role of multilingualism in academia and highlights the need to move beyond a solely communicative focus. By incorporating translanguaging practices and acknowledging students' diverse linguistic backgrounds, educational institutions can promote equitable access to education and foster social justice for multilingual learners.